Síndrome de Burnout em professores e alunos do programa de mestrado Ensino de Ciências da Amazônia: uma contribuição para formação de professores - Sampaio, Eliana Santos (2009)
The concern about the Teachers' and students' quality of life of the Amazon Science Teaching Master's Program of the University of the State of Amazonas – UEA motivated the investigation of the Burnout Syndrome (BS) proving the main problem of this work. Burnout is a result of exhaustion, deception and loss of interest for work that appears in the professions that maintain the direct contact with people. The teachers are the most professionals that are affected for this syndrome. With the objective of verifying the Burnout possibilities on those that are getting their masters degree (students) and the teachers, as well, the instruments that have been used (Questionnaires: CBP-R and MBI-ED) that emphasize the results in the Burnout's dimension: Emotional exhaustion (EE), Depersonalization (DE) and Professional Accomplishment (PA). The claimed theoretical conceptions by the authors have contributed for the construction of the theoretical reference and, as well, for the methodological passage of the research, when pointed out about the theoretical Burnout model. The results observed indicated that a teacher that is fine with his social and financial situation, but concerned about the ways that teaching and learning process are going to take, in contrast of the students, that revealed high isolated interested degree, besides the financial, personal and interpersonal difficulties at work, resulting of a conflict of interests. Besides other aspects related to the expectations on concluding the master's. The analysis of the results were very useful for the parameters of a products creation. It is about a easy-share media (DVD) with the objective of sharing information to identify and control the Burnout syndrome, that can contribute to minimize other conflicts resulting of a harmful behavior to the teacher's practical on Science Teaching.